Language Learning Shifts and Attitudes Towards Language Learning in an Online Tandem Program for Beginner Writers - Constanza Tolosa; Claudia Lucía Ordóñez; Diana Carolina Guevara (Universidad Nacional de Colombia, 2017)
We present findings of a project that investigated the potential of an online tandem program to enhance the foreign language learning of two groups of school-aged beginner learners, one learning English in Colombia and the other learning Spanish in New Zealand. We assessed the impact of the project on students' learning with a free writing activity done as pretest and posttest and used a semi-structured interview to explore their attitudes towards language learning and their perceived development of their native language. Data analysis indicated statistically significant gains in foreign language writing and positive attitudinal changes toward foreign and native language learning.